A Socialised Medical Service (London : The Socialist Medical Association, 1933)
1933 1933 1930s 21 pages supply of midwives is available in every district, together with doctors with adequate midwifery experience, and also consultants to assist them when required. There must be a sufficient number of maternity beds in well-equipped hospitals, and every effort must be made to induce as many women as possible to avail themselves of them. The Local Authority must be prepared to pay the whole or part of the cost of these Services when the patient is unable herself to meet them. Further, it will be desirable for the Minister of Health to exercise his powers and reinsure the contributions for Maternity benefit under the National Health Insurance Act, giving that benefit partly in cash and partly in Maternity services. In addition, it will be desirable to further extend and develop the Infant Welfare Services and also the services for the inspection and treatment of children between the ages of two and five — in other words, for those below school age. Mothers will be encouraged to bring their children for periodical examination, even when apparently in good health, and should diseased conditions be discovered, children will be either treated in the clinic, sent on to a specialist, or referred to the Home Doctor, as soon as the necessary State Service has been developed for this last. Pending the development of this State Service it will also be useful to extend the services of the School Medical Department until the age of entry into Insurance. Children leaving school will be instructed to attend at an evening clinic for examination once a year, and the necessary treatment given them as in the case of children still attending school. The administrative changes proposed in the earlier pages will also need to be carried out. It will probably be useful as a first step to constitute the Counties and County Boroughs as the sole administrative units for health purposes, and later, as a second step, to make a new authority representing both County and included County Boroughs the unit. Published by the SOCIALIST MEDICAL ASSOCIAION, 72 Balham Park Road, S.W.12, and printed by THE LONDON CALEDONIAN PRESS LTD., 74 Swinton Street, Gray's Inn Road, London, W.C.1. - w2902. 292/847/1/1